Arrows of time and fundamental symmetries in chemical physics12. Issue 3 (22nd May 2012) - Brändas, Erkki J.; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract The field of chemical and physical processes, using principal microscopic techniques, should today allegedly be identified as a fundamental branch of physics. The discipline, by tradition known as chemical physics, is undergoing rapid progress. This assessment, illustrated by the advances presented at this Congress, is characterized by modern developments and novel trends with a concrete bearing on original theoretical understanding, with the possibility to go beyond traditional interpretations and explanations. In this vein, we do not only consider nonrelativistic treatments of various types of molecules including interactions between these and polymers, theoretical examinations of chemical reactions, surface states and interface states, disordered phenomena etc., but also recent progress together with non‐Hermitean extensions to quantum mechanics and statistical mechanics. The latter leads to a united edifice of theoretical constructions including the law of self‐reference, which emerges in analogy with the illustrious Gödel theorem(s) of mathematical logic, that is, the assertion of the inherent limitations of all nontrivial axiomatic systems. The current development begets the foundation of temporal processes and associated invariance principles including the valuation of the various arrows of time. The present conjugate operator array formulation supports the possible gravitational origin of molecular chirality and other principal symmetry violations. © 2012 Wiley Periodicals, Inc.